2011
DOI: 10.1038/jid.2010.310
|View full text |Cite
|
Sign up to set email alerts
|

siRNA Knockdown of Ribonucleotide Reductase Inhibits Melanoma Cell Line Proliferation Alone or Synergistically with Temozolomide

Abstract: Systemically delivered small interfering RNA (siRNA) therapies for cancer have begun clinical development. The effects of siRNA-mediated knockdown of ribonucleotide reductase subunit-2 (RRM2), a rate-limiting enzyme in cell replication, were investigated in malignant melanoma, a cancer with a paucity of effective treatment options. A panel of human melanoma cell lines was transfected with siRNA to induce the knockdown of RRM2. Sequence-specific, siRNA-mediated inhibition of RRM2 effectively blocked cell prolif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 22 publications
3
27
0
1
Order By: Relevance
“…In addition, compared with the controls of no treatment and siNC 50 nM, cells treated with siRRM2 (50 and 25 nM) displayed a remarkable and dose-dependent increase in S-phase populations; and the G2/M-phase population decreased significantly (Figures 4E and 4F). This was consistent with the S-phase cell-cycle arrest matched with the mechanism of action, and it was in line with the reported data 31, 45. Synthesis of RRM2 protein is regulated in a cell-cycle-dependent fashion.…”
Section: Resultssupporting
confidence: 92%
“…In addition, compared with the controls of no treatment and siNC 50 nM, cells treated with siRRM2 (50 and 25 nM) displayed a remarkable and dose-dependent increase in S-phase populations; and the G2/M-phase population decreased significantly (Figures 4E and 4F). This was consistent with the S-phase cell-cycle arrest matched with the mechanism of action, and it was in line with the reported data 31, 45. Synthesis of RRM2 protein is regulated in a cell-cycle-dependent fashion.…”
Section: Resultssupporting
confidence: 92%
“…1). This is consistent with previous studies showing that RRM2 inhibition can reduce melanoma cell proliferation regardless of BRAF mutation status (12, 13). Melanoma cell proliferation was further decreased when combined with the BRAFi PLX4720 (Fig.…”
Section: Discussionsupporting
confidence: 93%
“…This suggests RRM2 plays a significant role in melanoma cell proliferation and tumor progression. Indeed, knockdown of RRM2 inhibits melanoma cell proliferation (12, 13). However, whether inhibition of RRM2 can prolong the treatment effect of BRAFi has not been explored.…”
Section: Introductionmentioning
confidence: 99%
“…RRM2 contributes to malignant cellular phenotype in a range of human cancers and its overexpression plays a critical role in tumor invasion (13,14). A previous study showed that sequence-specific small interfering RNA (siRNA)-mediated inhibition of RRM2 effectively blocked the cell proliferation and induced G1/S phase cell cycle arrest in melanoma cell lines (15). However, the biological functions of RRM2 in gastric cancer remain unclear.…”
Section: Introductionmentioning
confidence: 99%